CORPORALITY AND PHYSICAL EDUCATION: THE BODY THAT WANT TO EDUCATE (Fiep Bulletin - online, 2014)
The body, for Physical Education, means the union of being with being cognitive movement. Do we know that we are the body? Santos (2009) calls attention to how we understand that we are not owner of our body but we have a body that is able to think, feel and act and requires understanding of yourself and others. Embodiment is the human existence itself, is an attempt to understand the world through feelings structured to live in a society where "show" is a priority for some and uncomfortable for others. The school environment is a great facilitator of understanding body because bodies mingle and interact with each other by providing the knowledge, experience and exchange of body experiences. Body consciousness gives the individual the ability to learn and I can relate with each other, with objects and desires. Separating the man in their cognitive, motor and social job will not be possible since our body is complex and indivisible. Developing learning through this interaction body is or should be a common practice between knowledge and relationship. Embodiment has constituted one of the most interesting themes of reflection in education, especially physical education. (Vogel et al., 2009) and this practice are the stimuli for working relationships and provide students with a learning experience which consequently lead to improved performance. It will be up to the physical education teacher in the classroom to make sense of this body that needs thought and move to relate and survive in this space so much diversity and cultural differences. Knowing this body is to develop autonomy and present is able to survive culturally permeating an individual body to a body fully in line with society.
Keywords: corporeality; Physical Education; Education.